1963
DOI: 10.1677/joe.0.0270053
|View full text |Cite
|
Sign up to set email alerts
|

The Excretion of Neutral Steroids in the Urine of Newborn Infants

Abstract: Following enzyme hydrolysis of the urine of infants aged 1 to 6 days, the neutral steroids have been extracted and their excretion patterns determined using a method based on paper chromatography. Three groups of compounds have been estimated\p=m-\those reacting with Zimmermann reagent, those reducing blue tetrazolium and those giving sodium fluorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1964
1964
1973
1973

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…It atrophies at birth and is replaced by adult type of cells which are present in small amounts in the foetal gland. The metabolism of the adrenal hormones is different in the newborn, and the urinary steroids are very different from the usual adult pattern (Cathro, Birchall, Mitchell, and Forsyth, 1963). Examination of the urine does not give as much information about the activity of the suprarenal gland as later on in life, but there is evidence that the neonatal suprarenal will respond to stimulation (Klein, 1955) by ACTH or by stressful situations.…”
Section: Discussionmentioning
confidence: 99%
“…It atrophies at birth and is replaced by adult type of cells which are present in small amounts in the foetal gland. The metabolism of the adrenal hormones is different in the newborn, and the urinary steroids are very different from the usual adult pattern (Cathro, Birchall, Mitchell, and Forsyth, 1963). Examination of the urine does not give as much information about the activity of the suprarenal gland as later on in life, but there is evidence that the neonatal suprarenal will respond to stimulation (Klein, 1955) by ACTH or by stressful situations.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the recently reported isolation of 3/? :21-dihydroxypregn-5-en-20-one from neonatal urines (Cathro, Birchall, Mitchell & Forsyth, 1963) it seems likely that this condition persists in the new-born child. It is therefore doubtful to what extent, if any, the generalization made applies to early human life.…”
Section: Discussionmentioning
confidence: 99%
“…Ulstrom and colleagues (1960a) have shown that newborns produce relatively more of the polar metabolites of cortisol, mainly 6p-hydroxycortisol, and excrete them largely in the unconjugated form. Cathro, Birchall, Mitchell, and Forsyth (1963) found several unknown neutral steroids in the urine of newborn infants. One of these compounds has Adults,12 M, 0-3-1-1 gtg./100 ml.…”
Section: Ii-evaluation Of Adrenocortical Functionmentioning
confidence: 99%
“…Not many data are available (Paulsen and Sobel, 1960;Beas, Zurbrugg, Cara, and Gardner, 1962;Cathro et al, 1963;Visser, Crigler, and Gold, 1962;Kadar et al, 1964). These studies are only possible in research laboratories, but are essential in studying the metabolism of adrenal and gonadal androgens under varying conditions.…”
Section: Androgensmentioning
confidence: 99%